Rantai Pemasaran Ayam Kampung Super di Kabupaten Lampung Timur - Maria Herawati; Setiyowati (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2019)
This study aims to find out the super-native chicken marketing chain and to find out the marketing efficiency of super native chickens in East Lampung Regency. The research method is descriptive analytical method, which is a combination of descriptive methods and analytical methods. The study was conducted in April-May 2018. The results showed that there were three marketing chains of super-native chickens in East Lampung Regency, namely pattern I (farmers-collectors-small-consumer), pattern II (farmers-collectors / small collectors-consumer), and pattern III (farmers- consumer). The marketing margin for pattern I is Rp.27,500 / tail and pattern II is Rp.8,500 / tail. Marketing of super-native chickens in East Lampung Regency has been efficient with an efficiency value of 64.75 percent. Keywords: marketing chain, super-native chicken, marketing margin